2016
DOI: 10.3109/09546634.2016.1157257
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a novel phosphodiesterase inhibitor, E6005, in patients with atopic dermatitis: An investigator-blinded, vehicle-controlled study

Abstract: E6005 ointment showed anti-inflammatory efficacy in adult patients with atopic dermatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…The selective PDE-4 inhibitor RVT-501 has been shown to be clinically active in atopic dermatitis, with most common AE being local site reactions, nasopharyngitis, urticaria and acne [168][169][170][171]. The potential utility of this compound in lung cancer has also been demonstrated in a murine model of pulmonary inflammation, where an inhaled dry powdered formulation of E6005 when adminstered to mice resulted in suppression of neutrophilic pulmonary inflammation [172].…”
Section: E6005 (Rvt-501) (Eisai / Roivant)mentioning
confidence: 95%
“…The selective PDE-4 inhibitor RVT-501 has been shown to be clinically active in atopic dermatitis, with most common AE being local site reactions, nasopharyngitis, urticaria and acne [168][169][170][171]. The potential utility of this compound in lung cancer has also been demonstrated in a murine model of pulmonary inflammation, where an inhaled dry powdered formulation of E6005 when adminstered to mice resulted in suppression of neutrophilic pulmonary inflammation [172].…”
Section: E6005 (Rvt-501) (Eisai / Roivant)mentioning
confidence: 95%
“…PDE‐4 inhibitors will be available in both topical and oral forms. Topical PDE‐4 inhibitors, that is, Crisaborole, E6005 and DRM02 (ClinicalTrials.gov Identifier: NCT01993420) show promising results in clinical studies (details are shown in Table ). In addition, apremilast, an oral PDE‐4 inhibitor, achieved a decrease in EASI in a phase II study for AD …”
Section: New Drugs For the Treatment Of Admentioning
confidence: 99%
“…Unlike crisaborole, none of these investigational drugs contains boron; however, like crisaborole, they generally fall under the 500‐Dalton rule in terms of molecular weight, allowing for skin penetration (Figure ) . In addition, although promising results have been published for some of these agents, none has been evaluated in phase 3 studies.…”
Section: Pde4 Inhibitors Currently Available and In Development For Admentioning
confidence: 99%
“…E6005/RVT‐501 is a topical PDE4 inhibitor that has been evaluated in several phase 1/2 studies. Results have been promising in children and adults in Japan . For example, at 0.03% and 0.2% strengths, a significant reduction in Scoring of Atopic Dermatitis (SCORAD) index score was observed in adults aged 20‐60 years .…”
Section: Pde4 Inhibitors Currently Available and In Development For Admentioning
confidence: 99%